Agroecological cropping systems: decoloniality and resistance - Wilson, Alexandria Jeanne (2021)
The colonization of Latin America was a violent invasion that destroyed diverse cosmovisions and instituted monocultures not only in the fields, but in thoughts as well. The effects of colonization continue to this day through structures of modernity and coloniality, further invalidating diverse cosmovisions and instituting exploitative practices uniquely expressed in industrialized, so-called modern agriculture. With this form of agriculture, intensive monoculture farming systems to meet the demand of international commodity markets were created that have degraded and devalued the biodiverse farming systems created by indigenous and African people that value synergies between non-human beings, between human beings, and between human and non-human beings in nature. Monocultures promoted by industrialized agriculture disconnected ancestral and spiritual ties to the land. In Brazil, one of the major monocultures produced for commodity consumption is coffee. Coffee monocultures in the Zona da Mata of Minas Gerais, Brazil, were intensified during the Green Revolution and caused environmental degradation and increased social inequality. In recent decades, agroecology and peasant farming have encouraged the diversification of cosmovisions and agricultural practices that have ancestral or spiritual influence. In response to the issues created by industrialized coffee production, peasants, researchers, and NGO employees came together to design agroforestry systems for the region and established a strong agroecological movement. This dissertation sought to understand how the peasant ancestrality and spirituality contribute to break structures of coloniality, identify the characteristics of decolonial action present in agroforestry systems, and analyze how the themes of cooperation, nature, and biodiversity and its functions present through the agroforestry systems and can strengthen the resistance of farmers. To achieve these objectives, secondary data were analyzed using bulletins, called "Nossa Roça" bulletins, created through collective writing with agroecological farmers in the Zona da Mata. It was identified that the agroecological farmers of the Zona da Mata incorporate their ancestry, spirituality and religiosity into their agricultural practices, allowing them to resist colonial structures such as the pressure to use agrochemicals and modern perceptions of nature. Through actions and their cosmovisions, agroecological farmers of the Zona da Mata resist against and break structures of coloniality. Through these physical and epistemological acts, agroecological farmers sow the seeds of resistance and cultivate their own pluriverses, which, in this research, were considered decolonial acts. It was also identified that agroecological farmers used their agroforestry systems to reconnect with nature and increase the biodiversity of their agroecosystems. The connections to cooperation, nature, and biodiversity that agroforestry systems allowed farmers to create a break from colonial and modern perceptions. The design of agroforestry systems in the Zona da Mata could also present itself as the materialization of a pluriverse. Keywords: Coloniality. Agroforestry Systems. Ancestrality. Spirituality.Family Agriculture.